HEURISTIC AND THINK ALOUD TO EVALUATE USABILITY OF ACADEMIC INFORMATION SYSTEM - Satrio Agung Wicaksono; Retno Indah Rokhmawati; Mochamad Chandra Saputra; Raden Arief Setiawan (Universitas Trunojoyo Madura, 2017)
Academic Information System is an essential system in performing academic activities. Universitas Brawijaya are using Academic Information System named SIAKAD-UB. SIAKAD-UB is an information systems that deal with all kinds of student details and academic related reports. SIAKAD-UB encountered many problems along with the growth of data. This study aims to discover factor impact on problems of interface usability found in existing SIAKAD-UB using Heuristic Evaluation and Think Aloud method. This study involving 3 experts and 3 operators with the purpose of the evaluation received input from the experts and users. The result of experiment are find 3 problem heuristic with score 0 which mean no usability problem, 7 problem heuristic with score 1 which mean medium priority refinement, 7 problem heuristic with score 2 which mean low priority refinement, 7 problem heuristic with score 3 which mean high priority refinement. Heuristic evaluation and think aloud find 7 aspect refinement are Visibility of system status, Match between system and the real world, User control and freedom, Consistency and standards, Recognition rather than recall, Flexibility and efficiency of use, Help and documentation.